2004
DOI: 10.1074/jbc.m307046200
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens α-Toxin Activates the Sphingomyelin Metabolism System in Sheep Erythrocytes

Abstract: Clostridium perfringens ␣-toxin induces hemolysis of rabbit erythrocytes through the activation of glycerophospholipid metabolism. Sheep erythrocytes contain large amounts of sphingomyelin (SM) but not phosphatidylcholine. We investigated the relationship between the toxin-induced hemolysis and SM metabolic system in sheep erythrocytes. ␣-Toxin simultaneously induced hemolysis and a reduction in the levels of SM and formation of ceramide and sphingosine 1-phosphate (S1P). N-Oleoylethanolamine, a ceramidase inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 54 publications
1
49
0
1
Order By: Relevance
“…We have also demonstrated that the alpha-toxin-induced hemolysis of sheep erythrocytes is dependent on the activation of the sphingomyelin metabolic system through GTP-binding proteins, especially the formation of sphingosine 1-phosphate [22,23].Therefore, the toxin-induced activation of phospholipid metabolism through G protein is closely involved in the biological activities. In the present review, we demonstrate the relationship between phospholipid metabolism via G protein and the biological activities induced by alpha-toxin.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…We have also demonstrated that the alpha-toxin-induced hemolysis of sheep erythrocytes is dependent on the activation of the sphingomyelin metabolic system through GTP-binding proteins, especially the formation of sphingosine 1-phosphate [22,23].Therefore, the toxin-induced activation of phospholipid metabolism through G protein is closely involved in the biological activities. In the present review, we demonstrate the relationship between phospholipid metabolism via G protein and the biological activities induced by alpha-toxin.…”
Section: Introductionmentioning
confidence: 92%
“…Sheep erythrocytes contain large amounts of sphingomyelin (SM) but not PC. Alpha-toxin simultaneously induced hemolysis and a reduction in the levels of SM in the membrane and an increase in ceramide and sphingosine 1-phosphate (S1P) [22]. It seemed that the toxin-induced hemolysis of sheep erythrocytes is closely related to the hydrolysis of SM in the membrane by the SMase activity of alpha-toxin.…”
Section: Activation Of Sphingomyelin Metabolism Through Gtpbinding Prmentioning
confidence: 99%
See 2 more Smart Citations
“…SMase Activity Assay-The hemolytic activity of the enzyme was determined by the amount of hemoglobin released from sheep erythrocytes using a method described previously (17). The reaction mixture containing the enzyme at various concentrations, 3% (w/v) sheep erythrocytes, 20 mM Tris-HCl buffer (pH 7.5), 3 mM MgCl 2 , and 0.9% (w/v) NaCl, was incubated for 30 min at 37°C and then centrifuged at 500 ϫ g for 3 min in order to prepare the test aliquot.…”
Section: Methodsmentioning
confidence: 99%